Preparation method of medical PET (Polyethylene Terephthalate)
By using non-heavy metal catalysts and compound antioxidants in the preparation process of medical PET, and vacuum drum solid phase enhancement, the acetaldehyde content in medical PET was successfully reduced, the problem of excessive acetaldehyde content was solved, and safer medical PET application was achieved.
Patent Information
- Application Number
- CN202411880185.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
AI Technical Summary
The existing medical PET has a high acetaldehyde content, which is difficult to meet the requirement that the acetaldehyde content in the national standard for drug packaging shall not exceed two parts per million.
Dibasic acid and diol are used as raw materials, non-heavy metal catalysts such as germanium, titanium, magnesium, etc. are added, and composite antioxidants are combined for esterification polymerization, and solid-phase viscosity is increased by vacuum drum solid-phase viscosity enhancing device to reduce acetaldehyde generation.
It effectively reduces the acetaldehyde content in medical PET and achieves the effect of ultra-low acetaldehyde. The acetaldehyde content is measured at around 0.25μg/g according to the national standard "GB/T17931-2018", solving the safety hazards caused by excessive acetaldehyde content.
Smart Images

Figure CN119708445A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to polyethylene terephthalate (PET for short), in particular to a preparation method of medical PET, belonging to the technical field of polymer materials. Background Art
[0002] The State Food and Drug Administration has very strict requirements for medical packaging. The product performance requirements for pharmaceutical packaging materials are mainly: certain mechanical properties, packaging materials should be able to effectively protect products, so they should have certain strength, toughness and elasticity, etc., to adapt to the influence of static and dynamic factors such as pressure, impact, vibration, etc.; good barrier properties, according to different requirements for product packaging, packaging materials should have certain barriers to moisture, water vapor, gas, light, aroma, odor, heat, etc.; good safety performance, the toxicity of the packaging material itself should be low, so as not to contaminate the product and affect human health; packaging materials should be non-corrosive and have insect-proof, moth-proof, rodent-proof, and microbial inhibition properties to protect product safety; suitable processing properties, packaging materials should be easy to process and easy to make various packaging containers; packaging operations should be easy to mechanize and automate to adapt to large-scale industrial production; suitable for printing, easy to print packaging logos; good economic performance, packaging materials should be widely available, easy to obtain, and low cost, and packaging materials and packaging containers after use should be easy to handle, not pollute the environment, and avoid causing public hazards. Medical PET meets all of the above requirements.
[0003] In recent years, with the development of technology and the increase in consumer demand, the pharmaceutical packaging market has continued to expand, and various materials have been used in pharmaceutical packaging. Among them, medical PET has become an important packaging material in the pharmaceutical industry due to its excellent mechanical properties and chemical stability, excellent high and low temperature resistance, good gas barrier properties, and environmental protection. It has been recognized by the market, and medical PET bottle packaging is becoming more and more widely used.
[0004] At present, domestic medical PET is almost directly processed from bottle-grade PET chips, or processed after modification based on bottle-grade PET chips. However, the acetaldehyde content of ordinary bottle-grade PET chips and existing medical PET is high, and the high injection temperature leads to high acetaldehyde content in the product, which is difficult to meet the requirements of the acetaldehyde test method of the national standard for pharmaceutical packaging "YBB00282004-2015" that the acetaldehyde content shall not exceed 2 parts per million.
[0005] Refer to the Chinese invention patent application with application number 201410819190.X, entitled "A medical modified polyester masterbatch and its preparation method" (application publication number CN104448720A) and the Chinese invention patent application with application number 202110600826.1, entitled "A functional polyester masterbatch and its preparation method" (application publication number CN115477772A). None of the above documents mentioned related issues such as acetaldehyde content standards.
[0006] Reference is made to the Chinese invention patent application publication "Production Method of Low-Acetaldehyde Polyester Products" (Application Publication No. CN106589340A) with application number 201510675795.0, which discloses a production method of low-acetaldehyde polyester products. The production method uses dicarboxylic acid and diol as raw materials, uses a titanium catalyst to polymerize to obtain a polyester product, and then pre-crystallizes and solid-phase polymerizes to obtain a low-acetaldehyde polyester with an intrinsic viscosity greater than 0.8 deciliter / gram and an acetaldehyde content less than 1.0 ppmw.
[0007] See also the Chinese invention patent application with application number 202110603062.1, "A medical polyester and its production method" (application publication number CN115477830A). The document discloses a medical polyester and its production method. The method uses dibasic acid and diol as raw materials, and the raw materials, polymerization catalyst, colorant, and phosphorus stabilizer are mixed into a slurry and put into an esterification kettle. After esterification reaction and then polycondensation, a flow promoter is added to the side end of the melt pipeline at the outlet of the final reduction kettle and mixed with the polymer to obtain medical polyester chips with a characteristic viscosity of 0.55-0.70dL / g.
[0008] The existing technologies mainly adopt measures such as adding new substances into the medical PET carrier or changing the catalyst, but have not really produced ultra-low acetaldehyde medical PET, and have not clearly explained the acetaldehyde content testing problem. Summary of the invention
[0009] The technical problem to be solved by the present invention is to provide a method for preparing medical PET with ultra-low acetaldehyde content in view of the above technical status.
[0010] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing medical PET, characterized by comprising the following steps:
[0011] Using dibasic acid and diol as raw materials, adding non-heavy metal catalyst, compound antioxidant, phosphorus stabilizer to carry out esterification polymerization, pelletizing to obtain CP particles after the polymerization, and the CP particles enter the vacuum drum intermittent solid phase viscosity increasing device to complete solid phase viscosity increasing;
[0012] The aforementioned non-heavy metal catalyst is at least one of germanium, titanium, magnesium, aluminum oxide, alkyl compound, and halogen compound; the non-heavy metal catalyst is added in an amount of 50 to 300 ppm of the total weight of the polyester during the preparation process;
[0013] The aforementioned compound antioxidant is composed of the following components and their weight ratio: the molar ratio of hindered phenols, phosphites and thiols is 2-8:1:2-5, and the added amount during the preparation process is 0.1‰-1% of the total weight of the polyester.
[0014] The mainstream production process of PET is direct esterification, which is mainly divided into two stages: CP (esterification and polycondensation) liquid phase continuous polymerization and SSP (solid phase polycondensation viscosity enhancement). CP refers to the continuous esterification reaction and continuous polycondensation reaction of PTA, MEG, the third monomer IPA (isophthalic acid), colorant and thermal stabilizer in the liquid phase to produce bottle-grade basic chips, which are then subjected to SSP solid phase polycondensation reaction viscosity enhancement under heating to produce chips with higher crystallinity.
[0015] Preferably, the polymerization reaction temperature is 250° C. to 280° C., and the reaction time is 3 to 8 hours.
[0016] Preferably, the solid phase viscosity enhancement process includes a drainage drying period, a pre-crystallization period and a chain growth period in sequence. The temperature of the drainage drying period is 80-120°C, and the insulation time is 4-8 hours; the temperature of the pre-crystallization period is 140-170°C, and the insulation time is 6-12 hours; the temperature of the chain growth period is 185-210°C, and the insulation time is 18-26 hours.
[0017] Compared with the prior art, the advantages of the present invention are: by using a non-heavy metal catalyst, the heavy metal content in PET is reduced, and the generation of acetaldehyde is effectively catalyzed to reduce the terminal carboxyl value and the acetaldehyde generated during the injection molding process; a compound antioxidant is added to reduce the generation of acetaldehyde by thermal oxidation degradation during the production of PET, and the acetaldehyde generated during the injection molding process can be reduced; the reaction process is controlled to reduce the generation of acetaldehyde; a vacuum drum solid phase polycondensation device is used for solid phase viscosity increase, and most of the acetaldehyde in PET is extracted while the viscosity is increased; finally, medical PET with ultra-low acetaldehyde is obtained, and the acetaldehyde content is measured to be about 0.25 μg / g according to the national standard "GB / T17931-2018".
[0018] The present invention can solve the various safety hazards caused by the low acetaldehyde content of existing medical PET on the market and the sudden increase of acetaldehyde content after injection molding, so that medical PET can be used more safely and widely in the medical industry, and has broad application prospects in the field of pharmaceutical packaging. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is an integral graph of the results of gas chromatography measurement of acetaldehyde by the product in Example 1.
[0020] Figure 2 This is an integral graph of the results of gas chromatography measurement of acetaldehyde by the product in Example 2.
[0021] Figure 3 This is an integral graph of the results of gas chromatography measurement of acetaldehyde by the product in Example 3.
[0022] Figure 4 This is an integral graph of the results of gas chromatography measurement of acetaldehyde by the product in Example 4.
[0023] Figure 5 This is an integral graph of the results of gas chromatography measurement of acetaldehyde by the product in Example 5. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below in conjunction with embodiments and drawings.
[0025] The comparative example is ordinary PET, and Examples 1-5 are preferred examples of low acetaldehyde medical PET.
[0026] Comparative Example
[0027] 1000g of purified terephthalic acid and 429g of ethylene glycol were used as raw materials, antimony trioxide was used as polymerization catalyst, phosphoric acid heat stabilizer was added to prepare slurry and put into esterification kettle, the amount of antimony catalyst added was 200ppm of the total amount of PET; the amount of phosphoric acid heat stabilizer added was 10μg / g, the esterification reaction temperature was 220-240℃, after the esterification was completed, the polycondensation temperature was controlled to be 270-280℃, and after the polymerization was completed, the basic slices of PET were obtained by pelletizing. The relevant data were measured as shown in Table 1.
[0028] Example 1
[0029] 960g of purified terephthalic acid, 40g of purified isophthalic acid and 429g of ethylene glycol are used as raw materials, and germanium aluminum catalyst, phosphoric acid heat stabilizer and compound antioxidant are added to prepare slurry and put into an esterification kettle, wherein the germanium aluminum catalyst is germanium dioxide and ethylene glycol aluminum, the ratio is 3.9:1, and the addition amount is 210ppm of the total amount of PET; the addition amount of phosphoric acid heat stabilizer is 10μg / g; the compound antioxidant is 1010 antioxidant: 168 antioxidant: DSTP antioxidant = 7.8:1:2 (weight ratio), and the addition amount is 2.2‰ of the total amount of PET produced; the esterification reaction temperature is 220-240℃, after the esterification is completed, the condensation temperature is controlled to be 250-270℃, and after the polymerization is completed, the PET basic slices are obtained by pelletizing. The PET basic slices enter the vacuum drum intermittent solid phase adhesion device, stay at 80-120°C for 4 hours, stay at 140-170°C for 6 hours, stay at 185-210°C for 18 hours, and then cool down to obtain PET. The relevant data are shown in Table 1 below.
[0030] Example 2
[0031] 960g of purified terephthalic acid, 40g of purified isophthalic acid and 429g of ethylene glycol are used as raw materials, and germanium aluminum catalyst, phosphoric acid heat stabilizer and antioxidant are added to prepare slurry and put into an esterification kettle, wherein the germanium aluminum catalyst is germanium dioxide and ethylene glycol aluminum, the ratio is 3.5:1, and the addition amount is 250ppm of the total amount of PET; the addition amount of phosphoric acid heat stabilizer is 10μg / g, the compound antioxidant is 1010 antioxidant: 168 antioxidant: DSTP antioxidant = 7.2:1:3.2 (weight ratio), and the addition amount is 2‰ of the total amount of PET produced; the esterification reaction temperature is 220-240℃, after the esterification is completed, the condensation temperature is controlled to be 250-270℃, and after the polymerization is completed, the PET basic slices are obtained by pelletizing. The PET basic slices enter the vacuum drum intermittent solid phase adhesion device, stay at 80-120°C for 4 hours, stay at 140-170°C for 6 hours, stay at 185-210°C for 19 hours, and then cool down to obtain PET. The relevant data are shown in Table 1 below.
[0032] Example 3
[0033] 960g of purified terephthalic acid, 40g of purified isophthalic acid and 429g of ethylene glycol are used as raw materials, and germanium aluminum catalyst, phosphoric acid heat stabilizer and antioxidant are added to prepare slurry and put into an esterification kettle, wherein the germanium aluminum catalyst is germanium dioxide and ethylene glycol aluminum, the ratio is 3.4:1, and the addition amount is 260ppm of the total amount of PET; the addition amount of phosphoric acid heat stabilizer is 10μg / g, the compound antioxidant is 1010 antioxidant: 168 antioxidant: DSTP antioxidant = 7.4:1:2.8 (weight ratio), and the addition amount is 2.1‰ of the total amount of PET produced; the esterification reaction temperature is 220-240℃, after the esterification is completed, the condensation temperature is controlled to be 250-270℃, and after the polymerization is completed, the PET basic slices are obtained by pelletizing. The PET basic slices enter the vacuum drum intermittent solid phase adhesion device, stay at 80-120°C for 4 hours, stay at 140-170°C for 6 hours, stay at 185-210°C for 17 hours, and then cool down to obtain PET. The relevant data are shown in Table 1 below.
[0034] Example 4
[0035] 960g of purified terephthalic acid, 40g of purified isophthalic acid and 429g of ethylene glycol are used as raw materials, and germanium aluminum catalyst, phosphoric acid heat stabilizer and antioxidant are added to prepare slurry and put into an esterification kettle, wherein the germanium aluminum catalyst is germanium dioxide and ethylene glycol aluminum, the ratio is 3:1, and the addition amount is 300ppm of the total amount of PET; the addition amount of phosphoric acid heat stabilizer is 10μg / g, the compound antioxidant is 1010 antioxidant: 168 antioxidant: DSTP antioxidant = 7.7:1:2.7 (weight ratio), and the addition amount is 2‰ of the total amount of PET produced; the esterification reaction temperature is 220-240℃, after the esterification is completed, the condensation temperature is controlled to be 250-270℃, and after the polymerization is completed, the PET basic slices are obtained by pelletizing. The PET basic slices enter the vacuum drum intermittent solid phase adhesion device, stay at 80-120°C for 4 hours, stay at 140-170°C for 6 hours, stay at 185-210°C for 18 hours, and then cool down to obtain PET. The relevant data are shown in Table 1 below.
[0036] Example 5
[0037] 960g of purified terephthalic acid, 40g of purified isophthalic acid and 429g of ethylene glycol are used as raw materials, and germanium aluminum catalyst, phosphoric acid heat stabilizer and antioxidant are added to prepare slurry and put into an esterification kettle, wherein the germanium aluminum catalyst is germanium dioxide and ethylene glycol aluminum, the ratio is 3.6:1, and the addition amount is 220ppm of the total amount of PET; the addition amount of phosphoric acid heat stabilizer is 10μg / g, the compound antioxidant is 1010 antioxidant: 168 antioxidant: DSTP antioxidant = 7.6:1:2.8 (weight ratio), and the addition amount is 1.8‰ of the total amount of PET produced; the esterification reaction temperature is 220-240℃, after the esterification is completed, the condensation temperature is controlled to be 250-270℃, and after the polymerization is completed, the PET basic slices are obtained by pelletizing. The PET base slices enter the vacuum drum intermittent solid phase adhesion device, stay at 80-120°C for 4 hours, stay at 140-170°C for 6 hours, stay at 185-210°C for 18 hours, and obtain PET after cooling.
[0038] The relevant data are shown in Table 1.
[0039] Sample name Viscosity (dL / g) Terminal carboxyl group (mol / t) Acetaldehyde (μg / g) Comparative Example 0.632 37.6 58.23 Example 1 0.805 13 0.22 Example 2 0.811 13.8 0.22 Example 3 0.789 14.2 0.24 Example 4 0.806 13.7 0.23 Example 5 0.798 13.1 0.22
[0040] Figures 1 to 5 It is the integral graph of the result of gas chromatography measuring acetaldehyde in each embodiment.
[0041] As shown in Table 1 and the attached figure, after using the germanium aluminum catalyst and antioxidant, the terminal carboxyl value and acetaldehyde content of PET after the solid phase viscosity enhancement process are significantly reduced. This is because the catalyst and antioxidant can reduce the acetaldehyde produced by the thermal degradation and thermal oxidation degradation of PET, and the vacuum drum solid phase polycondensation device can efficiently extract acetaldehyde from PET particles while viscosity enhancement.
[0042] Acetaldehyde content test method: According to the national standard "GB / T 17931-2018" acetaldehyde test method, about 50g of sample is placed in a container filled with liquid nitrogen and cooled for about 10min. After taking out the sample, it is immediately crushed with a sample crusher to crush all the samples into particles with a diameter of less than 1.0mm, and the crushing time does not exceed 30s; purge the headspace bottle with nitrogen, then add about 0.5g of sample to the 20mL headspace bottle, quickly put the sample in the headspace bottle, and quickly press the lid on the headspace bottle with a capping device. The whole operation process should try to avoid air entering the headspace bottle; place the headspace bottle containing the sample in the cranial cavity of the headspace sampler, heat it to 150℃ and keep it at a constant temperature for 60min, and then introduce a certain amount of acetaldehyde thermal equilibrium vapor released from the sample into the gas chromatograph, and measure it according to the established conditions of the national standard. According to the acetaldehyde peak area of the sample in the gas chromatogram, the corresponding acetaldehyde mass is calculated on the standard working curve.
Claims
1. A method for preparing medical PET, characterized in that The steps include: Using dibasic acid and diol as raw materials, adding non-heavy metal catalyst, compound antioxidant, phosphorus stabilizer to carry out esterification polymerization, pelletizing to obtain CP particles after the polymerization, and the CP particles enter the vacuum drum intermittent solid phase viscosity increasing device to complete solid phase viscosity increasing; The aforementioned non-heavy metal catalyst is at least one of germanium, titanium, magnesium, aluminum oxide, alkyl compound, and halogen compound; the non-heavy metal catalyst is added in an amount of 50 to 300 ppm of the total weight of the polyester during the preparation process; The aforementioned compound antioxidant is composed of the following components and their weight ratio: the molar ratio of hindered phenols, phosphites and thiols is 2-8:1:2-5, and the added amount during the preparation process is 0.1‰-1% of the total weight of the polyester.
2. The preparation method according to claim 1, characterized in that The polymerization reaction temperature is 250° C. to 280° C., and the reaction time is 3 to 8 hours.
3. The preparation method according to claim 1, characterized in that The solid phase viscosity enhancement process includes a drainage drying period, a pre-crystallization period and a chain growth period in sequence. The temperature of the drainage drying period is 80-120° C. and the insulation time is 4-8 hours; the temperature of the pre-crystallization period is 140-170° C. and the insulation time is 6-12 hours; the temperature of the chain growth period is 185-210° C. and the insulation time is 18-26 hours.
Citation Information
Patent Citations
Medical modified polyester masterbatch and preparation method thereof
CN104448720A
Method for producing low-acetaldehyde polyester product
CN106589340A
Functional polyester master batch and preparation method thereof
CN115477772A
Medical polyester and production method thereof
CN115477830A